Epidemiology of ectopic pregnancy at Laquintinie Douala hospital (Cameroon): prevalence survey, clinical profile, therapeutic and transfusion issues - Essome, Henri; Nana, Théophile N.; Halle, Gregory E.; Egbe, Thomas O.; Boten, Merlin; Tocki, Grace T.; Foumane, Pascal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Pregnancy is a serious pathology of the first trimester of pregnancy and is the leading cause of death. The objective of our work was to determine the hospital prevalence of ectopic pregnancy (EP), to describe the epidemiological, clinical and therapeutic profile given the often-haemorrhagic context at Laquintinie Hospital in Douala. Methods: We carried out a retrospective study over 10 years, from January 1st, 2007 to December 31st, 2016, using the operating theatre registers and the files of patients admitted during this period for ectopic pregnancy in the gynaecology and obstetrics department of the Laquintinie Hospital in Douala. Results: A total of 905 cases of EP for 32,595 deliveries were recorded, for an overall incidence of 2.8%. EP mainly affected the age group of 25 to 35 (60.6%), single people (57.9%) and housewives (46.6%). The risk factors found were similar to those of cervical cancer, namely multiple sexual partners (80.4%), the precocity of sexual intercourse under 18 years (54.1%) and sexually transmitted infections (52.5%). The symptomatic triad (pelvic pain, amenorrhea and metrorrhagia) was found in 46.1% of cases with a respective order of frequency of 96.9%, 77.3% and 63.6% The management was essentially surgical by radical laparotomy (97% of cases). Two of the 07 deaths were due to religious considerations. Conclusions: EP remains a frequent pathology in our environment with a heavy toll of tubal amputations and death.